(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The specimens of Xylocopini contained in the collection of Institute of Entomology of Milan are 27, belonging to 3 subgenera of Xylocopa: Afroxylocopa, Koptortosoma, Xylocopa. From bibliography it can conclude that the faunistic records reported for X. violacea and X. valga are new, except those from Milan and Elba Island.